Earthquake Hazard Estimation for Road Tunnel in Northwest Himalayas - Saavedra-Flores, E; Avudaiappan-, S (Pontificia Universidad Catolica de Chile, Escuela de Construccion Civil, 2020)
Seismic hazard assessment of earthquake prone terrain is estimated in numerous ways for civil underground structures such as tunnels which receives little attention on the seismic zones of the country. The resemblance of the past behaviour of earthquake is seen in the present seismotectonic block, and this is considered for this study. With this, the magnitudes of future earthquakes and its effects are predicted with Matlab software. In order to emphasize the need for carrying out a detailed Seismic Hazard analysis in underground openings, a proposed communication (road) tunnel project located in Kashmir Himalayas (GPS coordinates of Latitude 32.20° to 37.20° N, Longitude 72.50° to 80.50° E) one of the highest seismic zones of the Country (zone-V, BIS-2002) was taken up and the results reported in the paper. The paper incidentally has brought to light the need for carrying out such detailed seismic analyses in a routine manner for underground structures to be constructed in the country particularly in higher seismic zones, besides adumbrating structural support measures required for the various ground classes in the proposed road tunnel at Kashmir in response to seismic loading and also recommending retrofitting for other structures already in existence. A spin off the study is expected to be in the area of refining seismic zonation of the country and micro-zonation studies that are slated for the future. © 2020